Comparing the Severity of Injury and Trauma Pattern between Scooter and Street Motorcycle Riders; a Prospective Cohort Study - Bahardoust, Mansour; Karimi Behnagh, Arman; Bagherifard, Abolfazl; Khodabandeh, Mehrdad; Emami, Sayed Ali; Ghasemi Assl, Shakiba; Najd Mazhar, Farid (Archives of Academic Emergency Medicine, 2021)
Introduction: The popularity of motorcycle riding in Iran is increasing. However, there is a lack of information about the safety of different motorcycle types. This study aimed to compare the severity of injury and trauma pattern between scooter (vespa) and street (standard) motorcycle riders. Method: In a prospective cohort study, a comparison of demographics, injury severity, trauma pattern, and clinical characteristics between 324 riders (162 Vespa and 162 standard motorcycles) admitted to emergency departments was undertaken. The risk factors associated with severe injuries in the two groups were also determined. An emergency medicine specialist determined the severity of trauma based on the abbreviated injury scale (AIS). Results: The Odds Ratio (OR) of severe injuries was significantly higher in the standard motorcycle riders’ group (OR: 3.09; 95% CI: 1.9-4.21; p: 0.013). The frequency of lower extremity fractures was significantly lower in the Vespa group (OR: 4.11; 95% CI: 2.01-6.25; p = 0.012). The frequency of admission to the intensive care unit was significantly higher in the standard motorbike riders’ group (OR: 1.64; 95% CI: 1.11-2.51; p = 0.033). The multivariate analysis indicated that motorcycle type, the speed at the time of the accident, use of helmet, and age of riders are the most important predictors of trauma severity in riders (p<0.05). Conclusion: The pattern of injury varies between standard and Vespa motorcycles. The standard motorcycle riders were prone to a higher risk of adverse outcomes such as severe injuries. Due to the particular structure of scooters, the rate of lower limb injuries was significantly lower than standard motorcycles.